Penguatan Literasi Digital melalui Pembelajaran Social Studies Berbasis E-learning pada Siswa Sekolah Dasar - Candra Dewi (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: The existence of the industrial revolution 4.0 brings changes so that human resources are able to compete on a global scale related to the development of information and communication technology. This development needs to be accompanied by digital literacy education so that children are able to use, be responsible and choose communication and information technology. This digital literacy needs to be applied to existing learning, one of which is e-learning-based social studies learning for elementary school students. The writing of this article uses a literature study method where in the process of completing this paper the author collects articles and journals related to the topic of discussion. Digital literacy includes knowledge of digital information both in producing and receiving information, skills and using digital devices. E-learning-based social studies learning continues to be developed for children in meeting learning needs in the era of the industrial revolution 4.0. However, e-learning-based social studies learning has been readjusted because there are several challenges that pose problems in e-learning-based social studies learning, both from the aspect of human resources, facilities and infrastructure as well as technical implementation. As a recommendation for the future in this e-learning-based social studies learning, the provision of adequate facilities and infrastructure as well as efforts to increase digital literacy for teachers and students must continue to be enriched plus also optimize the role of parents and the surrounding environment.Abstrak: Adanya revolusi industri 4.0 menghadirkan perubahan agar sumber daya manusia mampu bersaing dalam skala global terkait dengan perkembangan teknologi informasi dan komunikasi. Perkembangan ini perlu diiringi dengan pendidikan literasi digital agar anak-anak mampu menggunakan, bertanggung jawab dan memilih teknologi komunikasi dan informasi. Literasi digital ini perlu diaplikasikan pada pembelajaran yang ada salah satunya pada pembelajaran social studies berbasis e-learning pada siswa sekolah dasar. Penulisan artikel ini menggunakan metode studi literature dimana dalam proses penyelesaian karya tulis ini penulis mengumpulkan tulisan dan jurnal yang terkait dengan topik pembahasan. Literasi digital meliputi pengetahuan terhadap informasi digital baik dalam memproduksi maupun menerima informasi, keterampilan dan menggunakan perangkat digital. Pembelajaran social studies berbasis e-learning terus dikembangkan pada anak dalam memenuhi kebutuhan pembelajaran pada era revolusi industry 4.0. Meski demikian, pembelajaran social studies berbasis e-learning dilakukan penyesuaian kembali karena terdapat beberapa tantangan yang menimbulkan problematika pembelajaran social studies berbasis e-learning baik dari aspek sumber daya manusia, sarana dan prasarana maupun teknis implementasi. Sebagai rekomendasi ke depan dalam pembelajaran social studies berbasis e-learning ini adalah penyediaan sarana dan prasaran yang memadai dan juga upaya peningkatan literasi digital bagi guru dan siswa harus terus diperkaya ditambah juga mengoptimalkan peran orangtua dan lingkungan sekitar.